An Ontology for Sustainability Reporting Based on Global Reporting Initiative (GRI) G4 - Yaldo, Ilham Salman Yousif (Curtin University, 2015)
The aim of this research is to fill the gap by developing ontology for Sustainability Reporting based on GRI G4 Guidelines. The chief research question is: What is the best approach to developing an Ontological Model for the knowledge domain Sustainability Reporting? The main objective of this research is to develop such ontology for Sustainability Reporting based on GRI G4.The developed ontology for Sustainability Reporting was validated by applying it to existing business data.